Structure and function of the plasminogen/plasmin system - Castellino, Francis J.; Ploplis, Victoria A. (Thrombosis and Haemostasis, 2005)
Activation of the fibrinolytic system is dependent on the conversion of the plasma zymogen, plasminogen (Pg), to the serine protease plasmin (Pm) by the physiological activators urokinase-type Pg activator (uPA) or tissue-type plasminogen activator (tPA). The primary in vivo function of Pm is to regulate vascular patency by degrading fibrin-containing thrombi. However, the identification of Pg/Pm receptors and the ability of Pm to degrade other matrix proteins have implicated Pm in other functions involving degradation of protein barriers, thereby mediating cell migration, an important event in a number of normal e.g., embryogenesis, wound healing, angiogenesis, and pathological, e.g., tumor growth and dissemination, processes. Prior to the development of Pg-deficient mice, much of the evidence for its role in other biological events was based on indirect studies. With the development and characterization of these mice, and ability to apply challenges utilizing a number of animal models that mimic the human condition, a clearer delineation of Pg/Pm function has evolved and has contributed to an understanding of mechanisms associated with a number of pathophysiological events.
Keywords: Plasminogen; fibrinolysis; kringle domains; gene targeting; cell invasion